Managing and developing community sport - Platts, Chris; Wilson, Robert 1980- (Routledge, Taylor & Francis Group, 2018)
Can sport and physical activity (PA) be used to improve the communities we live in? How do community groups manage facilities that provide sport and PA? How can managers ensure the services they deliver meet the needs of their community? What role should community sport schemes paly in society? Answer these questions and more in this, the first textbook to focus on the theory and practitioners with expertise in sport management, sport development, the sociology of sport, PA programming and community coaching, this book outlines the best practice and explores contemporary issues relating to: Community enhancement through sport and PA; Leadership, enterprise and innovation; Budgeting and decision making; Event and facility management; Corporate social responsibility (CSR); Monitoring and evaluation. The book is divided into three sections: Part I provides an introduction to developing and managing community sport; Part II outlines the key issues and challenges that face those working in the sector; and Part III examines the leadership and management qualities needed to effectively manage and develop community sport. Insightful and user-friendly, Managing and Developing Community Sport is written in an easy to read style and is a vital resource for sport management practitioners or students hoping to work in community-level sport.